Local Administration of Caloric Restriction Mimetics to Promote the Immune Control of Lung Metastases. (20th June 2019) - Le Noci, Valentino; Sommariva, Michele; Bianchi, Francesca; Triulzi, Tiziana; Tagliabue, Elda; Balsari, Andrea; Sfondrini, Lucia
Abstract : Caloric restriction mimetics (CRMs), compounds that mimic the biochemical effects of nutrient deprivation, administered via systemic route promote antitumor effects through the induction of autophagy and the modulation of the immune microenvironment; however, collateral effects due to metabolic changes and the possible weight loss might potentially limit their administration at long term. Here, we investigated in mice local administration of CRMs via aerosol to reduce metastasis implantation in the lung, whose physiologic immunosuppressive status favors tumor growth. Hydroxycitrate, spermidine, and alpha-lipoic acid, CRMs that target different metabolic enzymes, administered by aerosol, strongly reduced implantation of intravenously injected B16 melanoma cells without overt signs of toxicity, such as weight loss and changes in lung structure. Cytofluorimetric analysis of lung immune infiltrates revealed a significant increase of alveolar macrophages and CD103+ dendritic cells in mice treated with CRMs that paralleled an increased recruitment and activation of both CD3 T lymphocytes and NK cells. These effects were associated with the upregulation of genes related to M1 phenotype, as IL-12 and STAT-1, and to the decrease of M2 genes, as IL-10 and STAT-6, in adherent fraction of lung immune infiltrate, as revealed by real-time PCR analysis. Thus, in this proof-of-principle study, we highlight the antitumor effect of CRM aerosol delivery as a new and noninvasive therapeutic approach to locally modulate immunosurveillance at the tumor site in the lung.